(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
, which suggests that purification process is not required to increase the performance of chelated ferrous ion drilling mud thinner. Key words: Oil palm empty fruit bunches, black liquor, purification, soda lignin, drilling mud thinner, rheological properties